An instance of productive overabundance: The plural of some Italian VN compounds. (March 2019) - Pellegrini, Matteo; Ricca, Davide
Abstract : This paper investigates a case of overabundance in the plural cell of an open subclass of Italian VN compounds. The empirical basis includes: (i) a 163-item list of relevant compounds, for which the relative frequency of cell mates has been estimated by means of Web data; (ii) a naming questionnaire based on visual input, with 30 images submitted to about 200 informants, including those of several objects whose names are scarcely established in the lexicon; (iii) a further questionnaire, adapted to each informant, asking for acceptability judgements to detect overabundance at the single speaker's level. Results show that the given subclass of VN compounds provides an instance of systematic and productive overabundance in the Italian morphological system, differently from the examples usually discussed for this language.